Bhuta Yajna Dalam Teks Aji Swamandala - Harsananda, Hari; Anak Agung Ayu Alit Widyawati (Sphatika: Jurnal Teologi, 2025)
Bhuta Yajna is part of the five Yajna ceremonies commonly performed in Bali. Through Bhuta Yajna, humans maintain the balance of nature, which is an implementation of the Tri Hita Karana teaching. One of the texts that discusses Bhuta Yajna is the Aji Swamandala text. The study of Bhuta Yajna in this text is a form of qualitative research that employs hermeneutic theory to analyze it, using the Aji Swamandala text as the primary source, which has been translated and transcribed.The form of Bhuta Yajna in the Aji Swamandala text includes Caru, specifically Caruning Sasih, which serves to harmonize time, and Tawur Kesanga, known as Caruning Palemahan, which functions to harmonize nature and maintain environmental peace.The theological meaning behind the practice of Bhuta Yajna is related to Totemism Theology, which originates from animism—the belief that spirits inhabit the entire world. In this theological perspective, animals and plants are considered suitable substitutes for human sacrifices in the effort to create a harmonious world.